Educational Games and Learning Effectiveness - Peixoto, Daniela C. C.; Resende, Rodolfo F.; Pádua, Clarindo Isaías P. S. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2017: Anais do XXVIII Simpósio Brasileiro de Informática na Educação, 2017)
Assessments of educational games have to take into account many aspects, including internal and external game mechanisms. This paper analyses the assessment methods incorporated in a specific Software Engineering educational game, named SPIAL. We used four assessment categories that are commonly found in the literature: aim, implementation, integration and primary type. We observed that the main assessment mechanisms incorporated in SPIAL is the score. Other mechanisms were applied mostly for guiding students during the learning process. In addition, the external evaluations did not consider internal actions of the game and were used mostly to certify the acquired skill. Such findings are in line with the mechanisms used in other Software Engineering educational games. This paper also provides insights for researchers in issues related to the definition of educational game assessment mechanisms and implementation in general, an example is the evaluation of the effective learning compared to the evaluation of the player’s perception of learning.